Hormone Replacement and Strength Training Positively Influence Balance During Gait in Post-Menopausal Females: A Pilot Study - Perry, Stephen D. (Asist Group, 2005)
This study examined the effects of hormone replacement combined with strength training on improving dynamic balance control in post-menopausal women. Thirty one participating post-menopausal women were divided into three groups (hormone replacement (HR), non-hormone replacement (NR) and control (CR) group). HR and NR groups were tested for muscle strength and balance control during gait, prior to training and following a six week lower body strength training program. Quadriceps muscle strength was evaluated as isokinetic peak torque (60°·sec(-1)) using a CYBEX NORM and balance control was evaluated by center of mass - base of support relationships and ground reaction forces during gait perturbations. Only the HR group showed significantly (p < 0.05) improved balance control during the initial phase of unexpected gait termination and single stance periods while walking across uneven terrain following training. The strength gains in the HR group tended to be greater than in the NR group over the six week training program, although neither group showed statistically significant increases. The CR group showed no significant differences between testing times. HR in post-menopausal females may enhance dynamic balance control when combined with a strength training program, even if no statistically significant gains in strength are achieved.